1988
DOI: 10.1038/333093a0
|View full text |Cite
|
Sign up to set email alerts
|

Intraorganellar calcium and pH control proinsulin cleavage in the pancreatic β cell via two distinct site-specific endopeptidases

Abstract: Insulin is produced from an inactive precursor, proinsulin, through initial endoproteolytic cleavage at sites marked by pairs of basic amino-acid residues. We report here that lysates of insulin secretory granules contain two distinct Ca-dependent acidic endoproteases; one (type I) cleaving exclusively on the C-terminal side of Arg 31.Arg 32 (B-chain/C-peptide junction), the other (type II) preferentially on the C-terminal side of Lys 64.Arg 65 of proinsulin (C-peptide/A-chain junction). The Ca and pH requirem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
286
2

Year Published

1990
1990
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 411 publications
(301 citation statements)
references
References 28 publications
13
286
2
Order By: Relevance
“…The direct effect of vitamin D might be mediated by binding of the circulating active form, 1.25(OH)D 3, to the pancreatic beta cell VDR, and activation of vitamin D within the beta cell by the 1-α-hydroxylase enzyme; alternatively, it may be brought about by an effect on insulin action through stimulating the expression of insulin receptors and enhancing insulin responsiveness for glucose transport [2]. The indirect effects of vitamin D can be mediated via regulating extracellular calcium and insulin secretion through calcium fluxes in the beta cells [26]. Vitamin D may also be involved in systemic inflammation processes, and improve insulin sensitivity and promote beta cell survival by directly modulating the effect of cytokines [2].…”
Section: Discussionmentioning
confidence: 99%
“…The direct effect of vitamin D might be mediated by binding of the circulating active form, 1.25(OH)D 3, to the pancreatic beta cell VDR, and activation of vitamin D within the beta cell by the 1-α-hydroxylase enzyme; alternatively, it may be brought about by an effect on insulin action through stimulating the expression of insulin receptors and enhancing insulin responsiveness for glucose transport [2]. The indirect effects of vitamin D can be mediated via regulating extracellular calcium and insulin secretion through calcium fluxes in the beta cells [26]. Vitamin D may also be involved in systemic inflammation processes, and improve insulin sensitivity and promote beta cell survival by directly modulating the effect of cytokines [2].…”
Section: Discussionmentioning
confidence: 99%
“…NIT-2 and NIT-3 cells) confirmed that this CPE mutation leads to inhibition of proinsulin conversion while suggesting that at least some proinsulin was directed to granules. 2 The mere presence of proinsulin in a putative storage compartment is not proof in itself of sorting to the regulated pathway. This can only be addressed by following the kinetics of secretion of newly synthesized (labeled) proinsulin/insulin.…”
Section: Table I Percentage Of Total (Pro)insulin-related Productsmentioning
confidence: 99%
“…Acknowledgments-We thank Dr. Edward Leiter (The Jackson Laboratories, Bar Harbor, ME) for sending a copy of the study by Varlamov et al 2 prior to publication.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Prohormone convertases are specific to the regulated secretory pathway and cleave prohormones in secretory granules. The prohormone convertase family member PC2 may be involved in hybrid precursor processing in GH 3 cells since these cells express this enzyme (Seidah et al, 1990), which, although displaying optimum activity at acidic pH, is also active in neutral environments (Davidson et al, 1988). The other major candidate endoprotease likely to be involved in processing pro-α-factor in GH 3 cells is furin.…”
Section: Discussonmentioning
confidence: 99%